2017
DOI: 10.1097/sap.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Osmidrosis Treatment Approaches

Abstract: Surgery treatment has been demonstrated as the most effective result for treating osmidrosis. Liposuction has been identified as the most effective treatment, with the lowest number of associated complications. Combining the curettage method was an effective option for lowering recurrence rate in surgery and liposuction treatments. Finally, laser treatment was not significantly associated with benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…A recent review with a meta-analysis (18) which includes forty studies published before February 2016 demonstrated that surgical modality was the most effective treatment for axillary bromhidrosis. Among the surgical modalities, liposuction was identi ed as the most effective method, with the lowest number of associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review with a meta-analysis (18) which includes forty studies published before February 2016 demonstrated that surgical modality was the most effective treatment for axillary bromhidrosis. Among the surgical modalities, liposuction was identi ed as the most effective method, with the lowest number of associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, medical treatments such as topical agents, systemic agents, and botulinum toxin A have temporary results in the treatment of AO [3,7]. Most patients seek a more permanent solution, which can be accomplished only by more invasive means.…”
Section: Discussionmentioning
confidence: 99%
“…To date, some strategies for the treatment of AO and AH have been developed, with variable efficacy [3]. A major concern about the treatment of AO and AH is the lack of clinical guidelines [3]. Overall, in the current literature, the clinical approach to AO and AH remains controversial, ranging from conservative medical to surgical choices [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more aggressive removal of apocrine glands leads to better outcomes, but it is also associated with a higher risk of developing complications, such as hematomas, seromas, infections, poor wound healing, and scar formation. With the progress of minimal invasive intervention and combination therapy in recent years, wound size could be smaller and the rates of common complications after AO surgery have been tremendously decreased to less than 4.5% (1.5%-4.5%) [21]. Therefore, in terms of efficacy and acceptable risks, surgical intervention remains the leading choice for managing AO.…”
Section: Introductionmentioning
confidence: 99%